\documentclass{article} \input{../../preamble} \begin{document} \begin{theorem}[Sum of Arithmetic Series] Let $(a_i)_{i \geq 0}$ be an arithmetic sequence with common difference $d$. Then for some $n \in \mathbb{N}$, $$\sum_{i=0}^n a_i = \frac{(n + 1)(a_0 + a_n)}{2}.$$ \end{theorem} \begin{proof} \href{Sequence/Arithmetic.lean}{Bookshelf.Real.Sequence.Arithmetic.sum_recursive_closed} \end{proof} \begin{theorem}[Sum of Geometric Series] Let $(a_i)_{i \geq 0}$ be a geometric sequence with common ratio $r \neq 1$. Then for some $n \in \mathbb{N}$, $$\sum_{i=0}^n a_i = \frac{a_0(1 - r^{n+1})}{1 - r}.$$ \end{theorem} \begin{proof} \href{Sequence/Geometric.lean}{Bookshelf.Real.Sequence.Geometric.sum_recursive_closed} \end{proof} \end{document}